Cut-soiler-preferential shallow subsurface drainage (PSSD): A novel technique of salinity management with no residue burning - Yadav, Gajender; Neha; Yadav, R. K.; Prasad, Govind; Rai, A. K.; Onishi, Junya (Indian Farming, 2025)
Soil salinization is a major cause of land degradation in irrigated areas, often reducing productivity and forcing field abandonment. Salinity build-up in the root zone results from saline irrigation, shallow groundwater, weathering, and poor drainage. Conventional measures such as leaching and drainage installation have limitations due to high cost and technical constraints. A novel method, cut-soiler based Preferential Shallow Subsurface Drainage (PSSD), offers an effective alternative. The tractor-operated cut-soiler uses surface residues as filling material to construct shallow (40–60 cm) drains that promote preferential removal of water and salts while simultaneously managing residues without burning. Cut-soiler was introduced in India under Japan International Research Centre for Agricultural Sciences (JIRCAS)-ICAR-Central Soil Salinity Research Institute (ICAR-CSSRI) collaborative research project. The findings of evaluation studies on salt removal effect of cut-soiler PSSD suggested that it can reduce soil salinity upto 60% in a semi controlled lysimeter simulation study and upto 50% in the field condition in three years. The subsequent effect of desalination on performances of tested crops is prominent and consistent. Unlike conventional subsurface drainage, it is low-cost, farmer-friendly, and can be applied at the individual farm level, making it a promising option for sustainable salinity and residue management.